Selective Synthesis of Primary Anilines from NH3 and Cyclohexanones by Utilizing Preferential Adsorption of Styrene on the Pd Nanoparticle Surface. Issue 32 (5th July 2019) - Koizumi, Yu; Jin, Xiongjie; Yatabe, Takafumi; Miyazaki, Ray; Hasegawa, Jun‐ya; Nozaki, Kyoko; Mizuno, Noritaka; Yamaguchi, Kazuya
Abstract: Dehydrogenative aromatization is one of the attractive alternative methods for directly synthesizing primary anilines from NH3 and cyclohexanones. However, the selective synthesis of primary anilines is quite difficult because the desired primary aniline products and the cyclohexanone substrates readily undergo condensation affording the corresponding imines (i.e., N ‐cyclohexylidene‐anilines), followed by hydrogenation to produce N ‐cyclohexylanilines as the major products. In this study, primary anilines were selectively synthesized in the presence of supported Pd nanoparticle catalysts (e.g., Pd/HAP, HAP=hydroxyapatite, Ca10 (PO4 )6 (OH)2 ) by utilizing competitive adsorption unique to heterogeneous catalysis; in other words, when styrene was used as a hydrogen acceptor, which preferentially adsorbs on the Pd nanoparticle surface in the presence of N ‐cyclohexylidene‐anilines, various structurally diverse primary anilines were selectively synthesized from readily accessible NH3 and cyclohexanones. The Pd/HAP catalyst was reused several times though its catalytic performance gradually declined. Abstract : A willing sacrifice : Primary anilines were selectively synthesized in the presence of supported Pd nanoparticle catalysts (e.g., Pd/HAP, HAP=hydroxyapatite, Ca10 (PO4 )6 (OH)2 ) by utilizing competitive adsorption unique to heterogeneous catalysis. When styrene serves as a hydrogen acceptor, various structurally diverse primary anilines can be selectively synthesized from readily accessible NH3 and cyclohexanones.